The comparison of CLC2000 and CLC50 databases in terms of landscape metrics - Szabó, Szilárd (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
In the course of our work we often use databases not made by us: freely available or buyable ones. Using them we can not often estimate the accuracy of our work and make false conclusions. As an example those map databases can be mentioned which are based on either actual field mapping or the interpretation of aerial photographs and satellite pictures. Our aim is to show by the example of two land cover databases – CLC50 as a buyable and elaborated and CLC2000 as a free but simplified database – that how different results are yielded using them. In the course of the study the class-level landscape metric parameters of each patch were determined and analysed statistically. The results prove that the landscape analytical conclusions are influenced significantly by the landscape metric parameters depending on the derivation of them. In the case of land cover categories of smaller areas CLC50 provides more accurate picture due to its elaboration. The degree of this accuracy is quantified in the case of 16 metrics. Based on the results we suggest CLC2000 for small- or mezoscale examinations. As far as possible the use of CLC50 is proposed.
Keywords: CLC50; CLC2000; landscape metrics